Accounting in a ‘New’ History: A Disciplinary Power and Knowledge of Accounting - Sukoharsono, Eko Ganis (Accounting Department,, 1998)
There has been a growing number of research studies in accounting history challenging accounting researchers to re-examine extant explanations for the sustained emergence of accounting (eg., Hopwood [1985], Loft [1986], Miller and O'leary [1987], Miller, et al [1991], Stewart [1992], Hopper and Macintosh [1993]. and Tyson [1993]). These studies have criticised some traditional histories which are